On Marshall-Olkin Extended Weibull Distribution - Hanan Haj Ahmad; Omar M. Bdair; M. Ahsanullah (Journal of Statistical Theory and Applications (JSTA), 2017)
In this paper, we introduce a new form of distributions called ”Marshall-Olkin Extended Weibull distribution” MOEW. We study some of its structural properties and the shape of its hazard rate function. We provide some methods of point estimation for the unknown parameters and discuss its asymptotic properties. Finally, numerical methods and simulations are used to compare between different methods of estimation, then we study the behavior of parameters under different sample sizes and different values of parameters.